1999
DOI: 10.1007/s003300050883
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of expanding haematoma of the lateral abdominal wall after blunt abdominal trauma

Abstract: We report a rare case of an expanding post-traumatic lateral abdominal wall haematoma. A superselective arteriogram of the deep circumflex iliac artery showed extravasation from the ascending branch, urging emergency therapy. Microcoil and Gelfoam embolisation was successfully performed. Haematomas of the abdominal wall can be divided in the common rectus sheath haematomas and the rare haematomas of the lateral abdominal wall. Differentiating both entities is essential, since there is a strong difference in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…14 Recently, several reports have demonstrated the successful use of gelfoam embolization. 6,7 In our cases, we were able to control the bleeding using transcatheter embolization. Control of bleeding helps avoid any unnecessary surgical stress, irrespective of the expansion of the hematoma.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…14 Recently, several reports have demonstrated the successful use of gelfoam embolization. 6,7 In our cases, we were able to control the bleeding using transcatheter embolization. Control of bleeding helps avoid any unnecessary surgical stress, irrespective of the expansion of the hematoma.…”
Section: Discussionmentioning
confidence: 91%
“…[3][4][5] Katsumori et al reported a spontaneous hemorrhage from a deep circumflex iliac artery, 6 and Lefere et al reported an expanding hematoma of the lateral abdominal wall after blunt abdominal trauma. 7 Irifune et al also reported an abdominal wall hematoma in an adolescent javelin thrower. 8 Iatrogenic hematomas from injuries to the deep circumflex iliac artery as a result of trocar placement during laparoscopic surgery have also been reported in recent years.…”
Section: Discussionmentioning
confidence: 95%
“…Parl SW et al, reported a case of DCIA related hemoperitoneum due to surgical drain placement after liver transplantation. They successfully treated the case with Transcatheter embolization of the branches of the DCIA by using Nbutyl cyanoacrylate [12]. In the present case, the deceased initially taken to a local private hospital where the vascular injury has not been detected.…”
Section: Discussionmentioning
confidence: 78%
“…Lefere et al, reported a case of expanding lateral abdominal wall hematoma following the rupture of the DCIA in blunt abdominal trauma. The hemoperitoneum due to injury to DCIA is very rarely reported [12]. Parl SW et al, reported a case of DCIA related hemoperitoneum due to surgical drain placement after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recurrences following surgical therapy have not been reported. Treatment by micro coil and gel foam embolisation has been reported by Lefere et al 11 for expanding haematoma of the lateral abdominal wall after blunt abdominal trauma.…”
Section: And200(17mentioning
confidence: 94%